Comorbid infections in patients with spondyloarthritis who received modern antirheumatic therapy (preliminary data) - M. M. Baranova; N. V. Muravyeva; B. S. Belov; S. I. Glukhova; T. V. Korotaeva (Научно-практическая ревматология, 2022)
Actuality. Data on the prevalence of comorbid infections (CI) in patients with spondyloarthritis (SpA) are few. Risk factors for CI has not been sufficiently studied.Objective. To evaluate the frequency of comorbid infections in patients with spondyloarthritis treated with biological drugs in the form of monotherapy or in combination with DMARD and/or GC.Subjects and methods. The study included 93 patients (55 men, 38 women; average age – 37.0±11.5 years). In 59 patients, AS was diagnosed, in 32 – PsA, in 2 – undifferentiated SpA and SpA associated with nonspecific ulcerative colitis. All patients received biological drugs in combination with DMARD and/or GC or without them. The patients were interviewed by a research doctor with fi lling out a unified questionnaire. Additional information was obtained from medical records.Results. The leading place in the structure of CI was occupied by respiratory tract infections and ENT organs, the 2nd place belonged to herpes viral infections, the 3rd to mycotic infection. Serious CI (SCI) were also represented mainly by injections of respiratory tract infections and ENT organs. A tendency to an increase in the frequency of pneumonia, tuberculosis, acute bronchitis, skin infections, genital organs and mycoses against the background of SpA compared to the period preceding the development of the disease (no significant differences were found) was revealed. 69% of patients noted a more severe course of previously observed CI. 47 patients reported the temporary cancellation of therapy due to the development of CI. 49% of patients have documented exacerbation of SpA. The number of cases of SCI against the background of SpA doubled (p=0.03). There was a positive correlation between the intake of GC and the development of mycoses (r=0.216; p=0.04); between the duration of taking GC and the development of eye infections (r=0.385; p=0.01); between the duration of taking methotrexate and the development of tonsillitis (r=0.25; p=0.03); between taking interleukin 12/23 inhibitors and the development of tonsillitis (r=0.261; p=0.01); between the duration of taking tumor necrosis factor α inhibitors (iTNF-α) and the development of otitis (r=0.287; p=0.01); between the number of consistently used iTNF-α and the development of otitis (r=0.273; p=0.02).Conclusion. The data obtained indicate the relevance of the problem of CI in SpA. Further studies are needed on a larger cohort of patients with an assessment of the effect of therapy on the incidence of CI and the search for risk factors for CI.